2015
DOI: 10.1002/anie.201505714
|View full text |Cite
|
Sign up to set email alerts
|

Facile Enzymatic Synthesis of Ketoses

Abstract: Studies of rare ketoses have been hampered by a lack of efficient preparation methods. A convenient, efficient, and cost-effective platform for the facile synthesis of ketoses is described. This method enables the preparation of difficult-to-access ketopentoses and ketohexoses from common and inexpensive starting materials with high yield and purity and without the need for a tedious isomer separation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 39 publications
0
52
0
1
Order By: Relevance
“…Rare sugars can be used as starting materials for the synthesis of potential natural products with important biological activities for applications in the food, pharmaceutical, medicinal, and chemical industries 1, 2 . Sugar 4-epimerization is a valuable reaction for the production of rare sugars and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Rare sugars can be used as starting materials for the synthesis of potential natural products with important biological activities for applications in the food, pharmaceutical, medicinal, and chemical industries 1, 2 . Sugar 4-epimerization is a valuable reaction for the production of rare sugars and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…18 We recently found that DTE from Pseudomonas Sp, St-24 also fails to use many ketose phosphates as the substrate. 1920 Therefore, we proposed that it may not recognize 6-deoxy-L-psicose 1-phosphate as substrate in this work. This assumption is supported by the purity analysis of 6-deoxy-L-psicose (Table 1).…”
mentioning
confidence: 95%
“…19 The main advantage of this method is that the products could be obtained in both high yield and purity without having to undergo an isomer separation step. The principle of this strategy is based on a “phosphorylation→dephosphorylation” cascade reaction.…”
mentioning
confidence: 99%
“…To address these problems, we recently developed a convenient, efficient and cost- effective platform for ketose synthesis, by which 10 non-readily available ketopentoses (L-ribulose, D-xylulose, D-ribulose, and L-xylulose) and ketohexoses (D-tagatose, D-sorbose, D-psicose, L-tagatose, L-fructose and L-psicose) were prepared from common and inexpensive starting materials with both high yield and purity without having to undergo a tedious isomer separation step. 15 The basic concept of this strategy is based on a “phosphorylation→dephosphorylation” cascade reaction. Thermodynamically unfavorable conversions were combined with targeted phosphorylation reactions by substrate-specific kinases to drive the conversions towards the formation of the desired ketoses.…”
mentioning
confidence: 99%
“…By screening the substrate specificity of many kinases, we recently found that fructose kinase (HK) from human, which phosphorylate ketose to ketose 1-phosphate, 26 preferred ketose with (3S)-configuration as its substrate. 15 In this work, substrate specificity of HK towards 6-deoxy-L-sorbose ((3S)-configuration), L-fucose ((3 R )-configuration), and L-fuculose ((3 R )-configuration) was studied (see Supplementary Information). 6-deoxy-L-sorbose could serve as the substrate of HK while no detectable activity of HK towards either L-fucose or L-fuculose was observed (Table 1), indicating its potential for one-pot multienzyme (OPME) reaction to produce 6-deoxy-L-sorbose from L-fucose.…”
mentioning
confidence: 99%